Symposium 12: Person Centered e-Learning in a Major Academic Course: What are the Results and What Can We Learn from Them? - Motschnig-Pitrik, Renate (Proceedings of the International Conference on Networked Learning, 2004)
During the last term, more than 300 students took part in a web-engineering course following a style that integrates e-learning elements into the Person-Centered e-Learning (PCeL) style developed at our department. The course serves as the focal object for tracing key aspects of the most recent action research cycle we conducted. This paper illustrates our way of combining theory and practice. In particular, we motivate our approach, sketch its socio-technical baseline, the patterns derived from the teaching/learning scenarios, experiences, students’ reactions and an empirical analysis of the project. We conclude that the situated use of technology in thoughtfully designed learning scenarios has the potential to increase students’ motivation and make learning more meaningful and pervasive. However, in order to add value to blended learning, instructors need well-developed interpersonal attitudes such as realness, respect and understanding.